2010
DOI: 10.21273/hortsci.45.7.1014
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Transformation of Taro (Colocasia esculenta) with a Rice Chitinase Gene Enhances Resistance to Sclerotium rolfsii

Abstract: Additional index words. particle bombardment, disease resistance, genetic engineering, agricultural biotechnology, tropical root crop Abstract. Genetic engineering has the potential to improve disease resistance in taro [Colocasia esculenta (L.) Schott]. To develop a method to produce highly regenerable calluses of taro, more than 40 combinations of Murashige and Skoog (MS) media at fullor half-strength with varying concentrations of auxin [a-naphthaleneacetic acid (NAA) or 2, 4-dichlorophenoxyacetic acid (2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Transformation of taro with the OxO gene. Using methods described earlier (He, 2006;He et al, 2008He et al, , 2010, calli were produced based on manipulation of plant hormones in tissue culture. In total, 200 pieces of calli (2 g) were transformed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation of taro with the OxO gene. Using methods described earlier (He, 2006;He et al, 2008He et al, , 2010, calli were produced based on manipulation of plant hormones in tissue culture. In total, 200 pieces of calli (2 g) were transformed.…”
Section: Resultsmentioning
confidence: 99%
“…Bioassay of transgenic plants challenged by Phytophthora colocasiae. Six-month-old transgenic plantlets (4 cm in height) of the transgenic line g5 or non-transformed plantlets were multiplied using tissue culture methods described in He et al (2010). The line g5 was selected initially for all bioassays, because it contained a single transgene based on Southern analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Transformation in Colocasia esculenta var. esculenta via microprojectile bombardment (He et al, 2004) and Agrobacterium tumefaciens (He et al, 2008) has also been reported. The efficiency of transformation via biolistics was reported to be very low with only one stably transformed plant generated while a slightly higher frequency of transformation was achieved via Agrobacterium where six stable transgenic plants were generated.…”
Section: Genetic Transformationmentioning
confidence: 96%
“…However, molecular characterization of plants derived from these gfp expressing embryos is yet to be done. The previous research groups (He et al, 2004;2008) used callus cultured on solid media as the target tissue for transformation which might have resulted in low frequency of transformation. Embryogenic suspension cultures are considered to be an excellent target tissue for genetic transformation since they (i) can be easily proliferated and thus provide ample target tissue, (ii) consist of small cell clumps allowing maximal exposure to the transforming agent thereby facilitating the identification of independent transformation events within the dispersed cell clusters under selection and (iii) allow the recovery of non-chimeric transformants due to the unicellular origin of embryos (Aguado-Santacruz et al, 2002;Sahrawat et al, 2003;ul-Haq, 2005).…”
Section: Genetic Transformationmentioning
confidence: 99%
“…Production of improved taro varieties via genetic transformation offers an attractive alternative to conventional breeding. This technique was successfully carried out using both Agrobacterium tumefaciens and microprojectile bombardment of regenerable embryogenic suspension [9]- [12] and regenerable callus [13] [14]. Tissue culture techniques are now an attractive field of biotechnological research, and their roles are presently exploited in the areas of large scale clonal propagation, crop improvement, and conservation of plant genetic resources.…”
Section: Introductionmentioning
confidence: 99%